Training of Trainers (ToT) on Policy Practices and Analysis to Support Implementation of Climate-Smart Agriculture (CSA) and Climate Information Services (CIS) Course Module - Ekepu, David; Nakayiwa, Florence Mayega; Majaliwa, Jackson Gilbert Mwanjalolo; Murungweni, Chrispen; Bonou, Alice (2025)
The training of trainers (ToT) on policy practices and analysis to support implementation of CSA and CIS was implemented virtually by RUFORUM on 15-17 April 2025. The overall goal of the module is to improve policy review, coordination and strengthen multi-level capacities to support implementation of CSA and CIS related policies and programmes. The virtual training lasted three days and was attended by 119 participants (69 male and 50 female). The participants came from 27 countries including Benin, Burkina Faso, Cameroon, Democratic Republic of the Congo (DRC), Egypt, Eswatini, Ethiopia, Hungary, Kenya, Liberia, Malawi, Mali, Mozambique, Namibia, Niger, Nigeria, Republic of Benin, Rwanda, Saudi Arabia, Sierra Leone, South Sudan, Sudan, Tanzania, Togo, Uganda, Zambia, and Zimbabwe. The training included four sessions: 1) Introduction to Policy and Policy Processes; 2) Inclusive Framework for Guiding Development and Implementation of CSA Policies and Programmes, 3) Monitoring, Evaluation and Review of CSA and CIS relevant policies and 4) Enabling Environment for Upscaling CSA and CIS. The course content was appreciated by participants, however requested additional topical areas to be included such as carbon markets and climate justice in future trainings implemented by RUFORUM.